Analysis of the Relationship Between Leg Muscle Strength and Flexibility and Headkick Results in Kickboxing Athletes in Kendal Regency - Aziz, Muhammad Saiful; Sungkowo, Sungkowo; Soedjatmiko, Soedjatmiko (Universitas Negeri Semarang, 2025)
The purpose of this study was to determine: 1) To analyze and describe the relationship between leg muscle strength and headkick results in kickboxing athletes in Kendal Regency. 2) To analyze and describe the relationship between flexibility and headkick results in kickboxing athletes in Kendal Regency. 3) To analyze and describe the simultaneous relationship between leg muscle strength and flexibility and headkick results in kickboxing athletes in Kendal Regency. The author employed a quantitative approach, employing a correlational method. The study was conducted at the Rubelsalu Sports Complex, Taman Khayangan Housing Complex, Svargaloka A 1-2, Jalan Semarang – Campurejo, Kendal Regency, with nine athletes as subjects. Multiple regression analysis was used to analyze the data at a 5% significance level. The estimated r value for the hypothesis 1 test was 0.250 < r table (0.05) (7) (0.666), concluding that there was no significant correlation between kick height and wall squat time in Kendal Regency Kickboxing athletes. The calculated r value of 0.984 > r table (0.05) (7) (0.666) was displayed in the results of the hypothesis 2 test, concluding that there was a significant correlation between flexibility and kick height in Kendal Regency Kickboxing athletes, although there was a fairly strong positive correlation descriptively. The results of the hypothesis 3 test obtained a calculated F result of 115.807 with F table = 5.14, so that F count > F table (1158.807 > 5.14) concluded that there was a significant correlation between leg muscle strength and flexibility with headkick results in Kendal Regency Kickboxing athletes.